2008
DOI: 10.1039/b804325f
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the first Li/halogen phosphinidenoid transition-metal complex

Abstract: Isolation and characterisation of the first Li/halogen phosphinidenoid transition-metal complex as well as low-temperature solution NMR, MAS-NMR experiments, DFT structures and calculated NMR chemical shifts are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 24 publications
2
40
0
2
Order By: Relevance
“…B. als Kontrastmittel in Bildgebungsverfahren in Betracht kommen. [11] Die Erforschung der Li/Cl-Phosphinidenoid-Komplexchemie [12][13][14][15][16] führte nun zur Entdeckung kurzlebiger P- [12,14] in die P-Chlorphosphinidenoid-Komplexe 2 a,b überführt und dann bei tiefer Temperatur mit Trityliumtetrafluoroborat umgesetzt. Langsames Aufwärmen ergab die Komplexe 5 und 6, die durch Säulen-chromatographie isoliert wurden.…”
unclassified
“…B. als Kontrastmittel in Bildgebungsverfahren in Betracht kommen. [11] Die Erforschung der Li/Cl-Phosphinidenoid-Komplexchemie [12][13][14][15][16] führte nun zur Entdeckung kurzlebiger P- [12,14] in die P-Chlorphosphinidenoid-Komplexe 2 a,b überführt und dann bei tiefer Temperatur mit Trityliumtetrafluoroborat umgesetzt. Langsames Aufwärmen ergab die Komplexe 5 und 6, die durch Säulen-chromatographie isoliert wurden.…”
unclassified
“…Phosgenation of 6a [15] (X = F, Scheme 2) led to selective formation of the desired complex 7b [δ ( 31 P) = 190.3 ppm, 1 J(P,F) = 915.5 Hz, 1 J P,W = 310.2 Hz]. Here, the half-lifetime in the reaction mixture at 25 °C was ca.…”
Section: Resultsmentioning
confidence: 98%
“…9 A 0.22 mmol portion of lithium diisopropylamide (freshly prepared with 0.14 mL (0.22 mmol) of a 1.6 M n-buthyllithium solution and 32 μL (0.22 mmol) of diisopropylamine) was dissolved in 3 mL of diethylether and cooled to −80°C. A cooled (0°C) solution of 107 mg (0.2 mmol) of 2a and 34 μL (0.2 mmol) of 12-crown-4 in 3 mL of diethylether was then added to the LDA solution via doubleended cannula.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…8c−f The case of phosphinidenes impressively illustrates (once more) the concept of transition-metal stabilization of reactive intermediates. Consequent adaptation of this concept to the case of phosphinidenoids enabled to firmly establish Li/X phosphinidenoid tungsten complexes (VI, X = F, 9 Cl 10,11 ) as a new class of highly reactive compounds in organophosphorus chemistry. 12 First studies on the reactivity of these species in solution had revealed nucleophilic reactivity in reactions with organic halides 10,11c,13 and terminal electrophilic phosphinidene complex-like behavior in reactions with π-substrates such as alkyne, carbonyl, and imine derivatives.…”
Section: ■ Introductionmentioning
confidence: 98%